2002
DOI: 10.1159/000058413
|View full text |Cite
|
Sign up to set email alerts
|

New Acetylcholinesterase Inhibitor (Donepezil) Treatment for Alzheimer’s Disease in a Chronic Dialysis Patient

Abstract: The new-generation acetylcholinesterase inhibitor, donepezil, is useful in the treatment of mild-to-moderate Alzheimer’s disease. A 72-year-old male chronic hemodialysis patient was diagnosed as having moderate Alzheimer’s disease. We administered donepezil at 3 mg/day orally to the patient. After 1 month’s treatment, the patient improved to a controllable psychiatric condition and was discharged from the hospital. The 24-hour plasma concentration profile of donepezil following the 3-mg once-daily dose varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It is known that donepezil is well absorbed, reaching peak plasma concentrations within 4 h [6]. A 5-h interval following donepezil administration might be beneficial to dialysis patients [7]. The results of 5 mg single-dose trials in patients with impaired renal function compared with patients from a healthy control group indicated no difference in pharmacokinetics of donepezil [32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that donepezil is well absorbed, reaching peak plasma concentrations within 4 h [6]. A 5-h interval following donepezil administration might be beneficial to dialysis patients [7]. The results of 5 mg single-dose trials in patients with impaired renal function compared with patients from a healthy control group indicated no difference in pharmacokinetics of donepezil [32].…”
Section: Discussionmentioning
confidence: 99%
“…We began donepezil administration with the lower dose of 2.5 mg/day orally and enhanced the dose to 5 mg/day 1 month later. Suwata et al [7] reported that whenever dialysis was starting 1 h after the administration of donepezil, an extraordinary elevation appeared in the plasma concentration time curve of donepezil, a fact that was not observed if donepezil was administered at least 5 h before the dialysis session. Taking into consideration these findings, we followed the same technique keeping, a 5-h interval between donepezil administration and dialysis session.…”
Section: Case Seriesmentioning
confidence: 99%
See 2 more Smart Citations